The important role of community organizations in stroke recovery and reintegration - Nelson, Michelle L. A.; MacEachern, Evan; Saragosa, Marianne (Frontiers in Stroke, 2024)
Stroke systems of care are grappling with pressures to ensure high-quality, evidence-informed, person-centered services with an emphasis on safe and timely discharge to the person's home and community. The literature describing the need for robust stroke systems has focused on services within the healthcare system, which are predominantly hospital-based and guided by the Medical Model. However, given the long-term nature of stroke recovery and the importance of attending to the challenges of resuming a meaningful life post-stroke, the involvement of community organizations becomes paramount in providing longer term support. This perspective paper explores the engagement of “community” within the context of stroke systems of care. It proposes that the community is both a destination of the pathway and a partner that can help address the ongoing and often unmet needs experienced post-discharge. Through these partnerships and collaborations, we suggest that community organizations can fill service gaps; volunteers could be leveraged to expand the breadth and quality of health and social services to meet the needs of stroke survivors and their families.